Dismantling Inequities in Adolescent and Young Adult Health through a Sexual and Reproductive Health Justice Approach - Barral, Romina; Kelley, Michele A.; Harrison, Megan E.; Svetaz, Maria Veronica; Efevbera, Yvette; Bhave, Swati; Kanbur, Nuray (Seminars in Reproductive Medicine, 2022)
This article provides an overview of the social determinants of adolescents and young adults' (AYAs') sexual and reproductive health (SRH), from a global health perspective. The status of AYAs' SRH constitutes leading health indicators across nations and globally, and reveals the well-being of this population. Throughout the article, AYAs' SRH is approached from a health equity perspective, which includes SRH health rights and reproductive justice. Using this health equity lens, salient topics are presented: sexual abuse/assault among AYAs; immigrant and refugee populations; child, early, and forced marriage; human trafficking; and female genital mutilation. The article also discusses access to SRH services and comprehensive education. Practical implications and resources are offered for healthcare providers for their daily encounters with AYAs, as well as for community, institutional level, and advocacy action. Healthcare providers are well positioned to advance AYAs SRH through mitigating inequities and in so doing, they are assuring the health of the population and future generations.
Keywords: adolescent and young adult; sexual and reproductive health; inequities; reproductive health justice; global health